In situ, broadband measurement of the radio frequency attenuation length at Summit Station, Greenland. Issue 272 (30th December 2022) - Aguilar, J. A.; Allison, P.; Beatty, J. J.; Besson, D.; Bishop, A.; Botner, O.; Bouma, S.; Buitink, S.; Cataldo, M.; Clark, B. A.; Curtis-Ginsberg, Z.; Connolly, A.; et al.
Abstract: Over the last 25 years, radiowave detection of neutrino-generated signals, using cold polar ice as the neutrino target, has emerged as perhaps the most promising technique for detection of extragalactic ultra-high energy neutrinos (corresponding to neutrino energies in excess of 0.01 Joules, or 10 17 electron volts). During the summer of 2021 and in tandem with the initial deployment of the Radio Neutrino Observatory in Greenland (RNO-G), we conducted radioglaciological measurements at Summit Station, Greenland to refine our understanding of the ice target. We report the result of one such measurement, the radio-frequency electric field attenuation length L_α . We find an approximately linear dependence of L_α on frequency with the best fit of the average field attenuation for the upper 1500 m of ice: L_α = ( ( 1154 ± 121) - ( 0.81 ± 0.14) ( ν /MHz) ) m for frequencies ν ∈ [145 − 350] MHz.